Iceland : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Iceland has benefited from the policy reorientation introduced just over a decade ago. The emergence of domestic and external imbalances in recent years, however, is cause for concern. An urgent task is to lower the risk exposure of the financial system. The adoption of an inflation targeting framework for monetary policy is commended. Fiscal policy should address the domestic and external imbalances. The intention to reinvigorate the privatization program is welcome. The government should continue to reduce the unfunded liability of the state employee pension scheme.